2016
DOI: 10.1080/17457289.2016.1243543
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective voting and party support at elections: credit and blame for government and opposition

Abstract: Retrospective voting is arguably one of the most important mechanisms of representative democracy, and whether or not the public holds the government accountable for its policy performance has been extensively studied. In this paper, we test whether retrospective voting extends to parties in the opposition, that is whether and how parties’ past performance evaluations affect their vote, regardless of whether they were in government or in opposition. Taking advantage of a rich set of questions embedded in a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 35 publications
1
38
0
Order By: Relevance
“…But who wins what government parties lose in tough times? We believe that, during a long-lasting crisis, the punishment extends itself beyond the incumbents, partially including even opposition parties, that cannot entirely capitalize from the retrospective mechanism (Plescia and Kritzinger, 2017). The space left for extrasystem volatility is not accidental, but proportional to the state of the economy.…”
Section: Resultsmentioning
confidence: 98%
“…But who wins what government parties lose in tough times? We believe that, during a long-lasting crisis, the punishment extends itself beyond the incumbents, partially including even opposition parties, that cannot entirely capitalize from the retrospective mechanism (Plescia and Kritzinger, 2017). The space left for extrasystem volatility is not accidental, but proportional to the state of the economy.…”
Section: Resultsmentioning
confidence: 98%
“…Albeit performance voting will not be absent in multiparty coalitions (Duch and Stevenson 2008), the literature has shown that not all incumbent parties are affected equally by retrospective voting (Debus et al 2014;Plescia and Kritzinger 2016;Plescia forthcoming). We will thus not treat the government as a unitary actor, but test our hypotheses at the party level, taking into account the performance evaluations of and ownership attribution to the various coalition parties.…”
Section: Hypothesis 2bmentioning
confidence: 99%
“…A recent line of literature demonstrates that this assumption is unrealistic. The literature shows that economic evaluations are much more strongly connected with vote choice for the PM's party compared with smaller coalition partners (Van der Brug et al, 2007;Fisher and Hobolt, 2010;Debus et al, 2014;Plescia and Kritzinger, 2017). Expanding on this, in an experimental study, and then Angelova et al (2016) with survey data from Germany, have confirmed that both prime ministerial dominance and ministerial proposal power are essential for policy responsibility attribution.…”
Section: Introductionmentioning
confidence: 92%